Backpropagation algorithm for rice yield prediction - Puteh, Saad; Mohamed Rizon, Mohamed Juhari; Nor Khairah, Jamaludin; Siti Sakira, Kamarudin; Aryati, Bakri; Nursalasawati, Rusli (Oita University, 2009)
Organized by Oita University, 28th - 30th January 2004 at Beppu, Oita, Japan.